Genosida Sebagai Pelanggaran Hak Asasi Manusia (HAM) Yang Berat - Gatot Eko Yudhoyono; Joko Setiyono (Fakultas Hukum, Universitas Warmadewa, 2024)
Deprivation of Human Rights using various criminal methods has been happening for a long time. Since then, many international regulations have set limits and prohibitions regarding war crimes up to genocide, including judicial bodies that are given responsibility for crimes that have been committed. By knowing the actions and bodies authorized to prosecute serious human rights violations, we can understand current changes in the existence of the crime of genocide. The aim of realizing international legal instruments is to fulfill the human rights of victims, the world community and perpetrators. The research method used is normative juridical. The research approach is through a statute approach, which examines problems using statutory regulations by analyzing relevant laws to be used as a legal basis, such as the Convention on the Prevention and Punishment of the Crime of Genocide in 1948, the Statute of the International Criminal Court in 1998 and the Law on Law Number 25 of 2000 concerning Human Rights Courts. The research results concluded that the crime of genocide is one of four serious human rights violations within the jurisdiction of the International Criminal Court. Genocide always involves two things, namely: objectively it refers to the act of extermination and subjectively the target of the action is a certain group. The International Criminal Court, in accordance with Article 34 of the 1998 Rome Statute, consists of four parts: The Presidency, the Chambers, the Offices of the Prosecutors and the Registry in carrying out its duties. The International Criminal Court will only carry out its functions if the National Court cannot carry out its functions properly, in this case the meaning is if the National Court does not want to try the perpetrator of the crime and unable.